KANDUNGAN BEBERAPA POLUTAN DAN KADAR DEBU PADA DAUN KETAPANG (Terminalia catappa L.) DI KOTA SAMARINDA PROVINSI KALIMANTAN TIMUR: The Pollutant and Dust Contents in the Leaves of Terminalia catappa L. in Samarinda City East Kalimantan Province - Yuliara Limbong; Karyati Karyati; Muhammad Syafrudin (PERENNIAL, 2021)
The vegetation has many roles, including the ability to reduce pollutants. Ketapang (Terminalia catappa L.) is a species of tree that is often recommended as a shade plant, because it has many advantages including as a pollutant reducing agent.The purposes of this study were to analyse the content of pollutants (lead (Pb), iron (Fe), and manganese (Mn)), and the dust content of ketapang leaves  and compare that pollutant and dust contents based on three area categories (highway, residential area, and vegetated area) in Samarinda City, East Kalimantan Province. The calculation of the number of vehicles that pass around the study site was carried out using the Traffic Survey application. Dimensional measurements of sample trees included diameter at breast height (DBH), tree height, and percentage of tree canopy. The analysis of pollutant contents was done by using AAS (Atomic Absorption Spectrophotometer) with a wet digestion process. The dust content was calculated using the formula where for the calculation of leaf area using millimeter blocks. The result showed that the highest Pb content (100.00 mg/kg), Fe content (347.00 mg/kg), and Mn content (564.00 mg/kg) were in ketapang leaves in Jalan M. Yamin, Jalan Pahlawan, and Jalan M. Yamin, respectively. The highest and lowest dust content were in ketapang leaves in Jalan Pahlawan (0.00316 g/cm2) and Perumahan Bumi Sempaja (0,00024 g/cm2). Based on the area categories, the highest Pb, Fe, Mn, and dust contents were in ketapang leaves that grow on the highway compared to residential and vegetated area. It can be caused by the large number of vehicles passing and canopy density. Information on the pollutant and dust contents in tree leaves can be taken into consideration in selecting plants in different areas.